Perirenal fat surface area as a risk factor for perioperative difficulties and 30‐day postoperative complications in elective colon cancer surgery. (23rd July 2018) - der Hagopian, O.; Dahlberg, M.; Heinius, G.; Nordberg, J.; Gustafsson, J.; Nordenvall, C.; Sandblom, G.; Farahnak, P.; Everhov, Å. H.
Abstract: Aim: Visceral obesity is associated with perioperative and postoperative complications in colorectal surgery. We aimed to investigate the association between the perirenal fat surface area (PRF) and postoperative complications. Method: Data on 610 patients undergoing curative, elective colon cancer resection between 2006 and 2016 at Stockholm South General Hospital were retrieved from a local quality register. We assessed perioperative and postoperative outcomes using a multinomial regression model adjusted for age, sex, American Society of Anesthesiologists classification and surgical approach (open/laparoscopy) in relation to PRF. Results: PRF could be measured in 605 patients; the median area was 24 cm 2 . Patients with PRF ≥ 40 cm 2 had longer operation time (median 223 vs 184 min), more intra‐operative bleeding (250 vs 125 ml), reoperations (11% vs 6%), surgical complications (27% vs 13%) and nonsurgical infectious complications (16% vs 9%) than patients with PRF < 40 cm 2, but there were no differences in the need for intensive care or duration of hospital stay. The multivariate analyses revealed an increased risk of any complication [OR 1.68 (95% CI 1.1–2.6)], which was even more pronounced for moderate complications [Clavien–Dindo II, OR 2.14 (CI 1.2–2.4]; Clavien–Dindo III, OR 2.35 (CI 1.0–5.5)] in patients with PRF ≥ 40 vs < 40 cm 2 . The absolute risk of complications was similar in men and women with PRF ≥ 40 cm 2 . Conclusion: PRF, an easily measured indirect marker of visceral obesity, was associated with overall and moderate complications in men and women and could serve as a useful tool in the assessment of preoperative risk.